SIX2 promotes cell plasticity via Wnt/β-catenin signalling in androgen receptor independent prostate cancer - Leppänen, Noora (Oxford University Press, 2025)
The use of androgen receptor (AR) inhibitors in prostate cancer gives rise to increased cellular lineage plasticity resulting in resistance to AR-targeted therapies. In this study, we examined the chromatin landscape of AR-positive prostate cancer cells post-exposure to the AR inhibitor enzalutamide. We identified a novel regulator of cell plasticity, the homeobox transcription factor SIX2, whose motif is enriched in accessible chromatin regions after treatment. Depletion of SIX2 in androgen-independent PC-3 prostate cancer cells induced a switch from a stem-like to an epithelial state, resulting in reduced cancer-related properties such as proliferation, colony formation, and metastasis both in vitro and in vivo. These effects were mediated through the downregulation of the Wnt/β-catenin signalling pathway and subsequent reduction of nuclear β-catenin. Collectively, our findings provide compelling evidence that the depletion of SIX2 may represent a promising strategy for overcoming the cell plasticity mechanisms driving antiandrogen resistance in prostate cancer.